Medical imaging in problem-based learning and impact on the students: cross-sectional study - Alduraibi, Sharifa Khalid; El Sadik , Abir; Elzainy, Ahmed; Alsolai, Ahmed; Alduraibi, Alaa (Journal of the Pakistan Medical Association, 2022)
Objective: To investigate the medical students’ performance with and perception towards different multimedia medical imaging tools. Method: The cross-sectional study was conducted at the College of Medicine, Qassim University, Saudi Arabia, from 2019 to 2020, and comprised third year undergraduate medical students during the academic year 2019-2020. The students were divided into tow groups. Those receiving multimedia-enhanced problem-based learning sessions were in intervention group A, while those receiving traditional problem-based learning sessions were in control group B. Scores of the students in the formative assessment at the end of the sessions were compared between the groups. Students’ satisfaction survey was also conducted online and analysed. Data was analysed using SPSS 21. Result: Of the 130 medical students, 75(57.7%) were males and 55(42.3%) were females. A significant increase in the mean scores was observed for both male and female students in group A compared to those in group B (p<0.05). The perception survey was filled up by 100(77%) students, and open-ended comments were obtained from 88(88%) of them. Overall, 69(74%) subjects expressed satisfaction with the multimedia-enhanced problem-based learning sessions. Conclusions: Radiological and pathological images enhanced the students’ understanding, interaction and critical thinking during problem-based learning sessions. Key Words: Radiological images, PBL sessions, Medical students, Qassim University, Medical imaging.